Analysis of Teacher Needs for the Development of Higher Order Thinking Skill (HOTS) Based Class X High School Chemistry Material Assessment Instruments - Saputra, Oddy Azis; Nurfajriani, Nurfajriani; Sudrajat, Ajat (Universitas Lampung, 2024)
This research aims to describe teachers' needs for HOTS-based assessment instruments that can be used in evaluating student learning outcomes in class X SMA. Needs analysis is carried out based on the first stage of the ADDIE model, namely (Analyst). The methods used in this research are survey and interview methods. The participants in this research were 5 chemistry teachers from 5 schools in Medan City. Data collection was carried out using a questionnaire with qualitative data type. The research results were analyzed descriptively and obtained data that the assessment instruments often used by teachers were still at the C1 - C3 cognitive level with a percentage of 90%, while HOTS-based chemistry learning assessment instruments with C4 - C6 cognitive levels were still very rarely used. The obstacle is that the creation, use and development of instruments are relatively difficult, so teachers feel less interested in creating HOTS-based assessment instruments and lack ideas or references for what assessment instruments are good for evaluating chemistry learning. So it has an impact on the level of critical and creative thinking abilities of students.Keywords: instrument, assesment, HOTSDOI: 10.23960/jppk.v13.i1.2024.14